GREEN BRAND INNOVATIVE ON GREEN BRAND LOYALTY: A Moderating Model Evaluation by Green Perceived Value of Indonesian Consumers for The Body Shop Products - Yunfajri Rahma Nofiasari; Ratni Prima Lita; Verinita Verinita (Halu Oleo University, 2023)
This study aims to analyze and prove green brand innovative impact on brand loyalty of Indonesian consumers for the Body Shop product, it also tested the moderating effect of green perceived value on its relation. In the sampling technique, this study used convenience sampling with online method questionnaire distribution. Recorded as many as 111 users of the Body Shop products across Indonesia (West, Mid, East) have participated. Then, the feedback was analyzed with the technique of SEM with the assistance of the Smart-PLS software's latest version. Results found that green brand innovation has a positive impact on green brand loyalty of Indonesian users for the Body Shop products, and green perceived value also has a positive impact on green brand loyalty. Unfortunately, green perceived value isn’t able to moderate the relationship between green brand innovation and green brand loyalty.